Factors influencing the Bidayuh’s community development and social capital interaction in achieving sustainable indigenous tourism in Sarawak, Malaysia - Johari, Shazali (2015)
This study is aimed to determine the antecedents of Bidayuh’s community development and social capital interaction in achieving sustainable tourism. The selected area for this study is Kampung Krokong Tringgus, Bau District in Sarawak. This village is well known for their Fairy Cave exploration and rock climbing, and it is an established tourism destination in Malaysia occupied by the Bidayuh ethnic community. The problem statement highlighted based on the personal communication with the leaders of the community and theoretical gap in the past studies. Lack of understanding on the issues of resource scarcity, empowerment, participation and/sustainability faced by the local community are clear gaps of the study. Thus, the general objective of the study is to capture the underlying factor of Bidayuh’s community development and social capital interaction in achieving sustainable tourism. Mixed method approach used with a combination of both qualitative and quantitative methods. The first part of the study is treated as an inductive approach, detailing data collected through in-depth interviews with 12 key informants. The interview data which had been transcribed and translated was analysed using thematic analysis technique. Thematic analysis revealed that there are five community resources that are important to the Bidayuh community to sustain their tourism practice. The five community resources identified are the natural resources, cultural resources,human resources, financial resources and infrastructure resources. Cultural resources have been the most important asset of the Bidayuh’s community to run tourism successfully. Next, the analysed qualitative data was put under deduction process using quantitative procedures. In inferential analysis, the results from the analysis and multiple regressions analysis were produced. After finding that all the independent variables are correlated with the dependent variables, multiple regression analysis was conducted. The findings of the multiple regressions analysis show that six independent variables were found to be significant predictor of sustainable indigenous tourism, andthese includes; natural resources, indigenous knowledge, bonding, bridging,participation, empowerment, and capacity building. The findings of this study support the generally discussed theories within the scope of community development and tourism development. This study does not contradict against the social capital theory. The community strongly feels that bridging, bonding and linking are very important to run tourism in sustainable manner. However, the unique contribution to the theory can be seen from the outcome of the Multiple Regression Analysis stating that empowerment, participation and community resources are also important to encourage sustainable tourism. By giving specific attention to the significant factors determining sustainable indigenous tourism in terms of community resources, indigenous tourism,cultural aspects, economic aspects, this aspect could be addressed.